A parallel solution for systems of integral equations - Pasin, Marcelo; Padoin, Edson Luiz (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2001: Anais do XIII Symposium on Computer Architecture and High Performance ComputingDO - 10.5753/sbac-pad.2001.22189, 2001)
This paper presents a parallelization of a numeric method for solving systems of integral equations. The algorithm was originally developed to find transitions of superconductor properties based on environment conditions. The sequential numerical method presents a wide range of parallelization levels, with irregular processing costs. A parallel implementation of it has the oportunity of adapting the parallel grain, compromising load-balancing and communication, and achieving better efficiency.